Studi Karakteristik Konselor Di Era Disrupsi: Upaya Membentuk Konselor Milenial - Mustaqim, Azmi (IAIN Kudus, 2019)
THE STUDY OF COUNSELORS’ CHARACTERISTICS IN THE ERA OF DISRUPTION: EFFORTS TO FORM MILLENNIAL COUNSELORS. This paper attempts to reformulate counselors’ characteristics in the era of disruption. The author tries to offer the idea of millennial counselors as a model of counselor characteristics based on millennial generation characteristics. The author believes that this is important because the development of internet technology causes changes in human life. McLuhan's technology determinism theory is used as a framework for deeper understanding that the discovery or development of communication technology was a factor which influence human culture. This study concludes that the reconstruction of the counselor’s characteristics in the disruption era is important since the differences of generations’ characteristics among humans separated by technological developments. The characteristics of millennial counselors include: having spirituality maturity, high sensitivity to technology, open-minded, respect, and tolerance, having freedom, high integrity, collaborative and innovative. These characteristics are not a perfect model but are dimensions of other characteristics that need to be achieved.Keywords: Counselor, Millennial Generation, Disruption Era